Medición y evaluación en comunicación estratégica en la Pontificia Universidad Católica del Ecuador Sede Santo Domingo - Vera Zambrano, Lucía Lelibeth (2014)
This research aims to contextualize the importance of strategic planning in organizational communications in 2013, at the Pontificia Universidad Católica del Ecuador sede Santo Domingo, province of Santo Domingo de los Tsáchilas. The methods used were: exploratory, descriptive, inductive and deductive qualitative thereby strengthening compliance with the general and specific objective; the project consists of four fundamental chapters, the institutional framework established in Chapter I, Chapter II the theoretical framework, the research is grounded through the methodological contributions on the subject, Chapter III presents the methodology used to development of investigative work, and Chapter IV diagnostic analysis raised about the survey to obtain information on strategic communication planning in the institution. The main conclusion was to raise an improvement in communication strategies used by the Department of Communication in the PUCESD, improving the relationship of information within and outside the institution.